2018
DOI: 10.1159/000491622
|View full text |Cite
|
Sign up to set email alerts
|

SKP2 Promotes Hepatocellular Carcinoma Progression Through Nuclear AMPK-SKP2-CARM1 Signaling Transcriptionally Regulating Nutrient-Deprived Autophagy Induction

Abstract: Background/Aims: SKP2 overexpression has been associated with poor prognosis in numerous cancers. The mechanisms of autophagy in the tumor pathogenesis have been a research focus recently. How the SKP2 involved in autophagy expresses oncogenic characteristics, especially in HCC, are largely unclear. Methods: The expression of SKP2 was detected by qPCR, Western blot, Immunohistochemical (IHC) and Immunofluorescence (IF) techniques. SKP2 was knocked down or overexpressed by lentivirus transfection in HCC cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…Nuclear inclusions in hepatocellular carcinoma correlate with survival nuclear AMPK-SKP2-CARM1 signalling was also reported in HCC autophagy [41].…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Nuclear inclusions in hepatocellular carcinoma correlate with survival nuclear AMPK-SKP2-CARM1 signalling was also reported in HCC autophagy [41].…”
mentioning
confidence: 71%
“…Intriguingly, studies of Shin et al showed that co‐activator‐associated arginine methyltransferase 1 (CARM1)‐dependent histone arginine methylation is a crucial nuclear event in autophagy . Induction by nuclear AMPK‐SKP2‐CARM1 signalling was also reported in HCC autophagy .…”
Section: Discussionmentioning
confidence: 99%
“…Skp2 has been demonstrated to enhance tumor progression and development via the regulation of various biological processes, namely cell proliferation, the cell cycle, apoptosis, invasion and metastasis (4)(5)(6). In liver cancer, the expression of Skp2 is associated with histological grade and tumor size, suggesting that Skp2 may be a prognostic biomarker for patients with liver cancer (7,8). A recent study demonstrated that Skp2 promoted the proliferation, colony formation, migration and invasion of liver cancer cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…In liver cancer, the expression of Skp2 is associated with histological grade and tumor size, suggesting that Skp2 may be a prognostic biomarker for patients with liver cancer (7,8). A recent study demonstrated that Skp2 promoted the proliferation, colony formation, migration and invasion of liver cancer cells (8). Therefore, Skp2 may be a potential target in the treatment of liver cancer.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in p27 Kip1 has been found to significantly reduce Mixed-Lineage Leukemia self-renewal ability, promote the monocytic differentiation of leukemic blasts, and induce cell death [5]. Skp2 has shown important roles in the development and progression of tumors as it was found to be frequently overexpressed in various human malignancies like hepatocellular carcinoma, breast cancer, lung cancers, prostate cancer, and osteosarcoma [2,[6][7][8][9][10][11]. In hepatocellular carcinoma, Skp2 was identified at a significantly increased level compared with paired normal tissue, and was correlated with tumor grade, size, and metastases.…”
Section: Introductionmentioning
confidence: 99%